Bound within Borders or Free as a Bird? Karen Life in Refugee Camps on the Thai–Burma Borderlands. Issue 4 (8th August 2021) - Bird, Jessica Nancy
ABSTRACT: Some residents of Thai–Burma border refugee camps regard themselves as caged birds—as prisoners of war—with little or no freedoms. External imaginations of camp residents as bound within borders are also common. This paper provides another perspective. It argues that residents subvert camp limitations; it describes how they stretch life beyond borders. Despite their armed monitoring, camp borders are contested by outwardly connecting, using tactics of transnationalism and translocalism; in essence, cross-border mobility. Such tactics provide freedom in an otherwise incarcerated camp-life and empower people in an otherwise powerless world. They enable individual actors to change their socio-political narrative. Naturally, severely isolated and restricted camps have low morale and residents have little hope. Given the relative permanence of Thai–Burma border camps (now in their fourth decade of existence), and an annual downward trend in their international aid, I recommend policy that ensures consistently clear channels of connection to life beyond camps' borders. This paper contributes to the borderlands debate by adding camp borders as another framework for investigation; it reflects on geopolitical contexts and shifting political landscapes impacting on cross-border mobility; and underscores the agency and self-determination of the Karen people from Burma.